(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Traditional life cycle assessment (LCA) is too data intensive and time consuming to be used during typical building design processes. Conducting an LCA during the building design process therefore requires simplifications and assumptions. Such “screening LCAs” are quicker and can be used with less data but introduce greater uncertainty. Unfortunately, uncertainty is not reflected in standard deterministic LCA calculations, which produce single-point values in LCA results. Thus, in this study, data quality scoring has been incorporated into a screening LCA to produce probabilistic predictions of environmental performance based on limited data. The approach has been applied during the design process of a bio-based wall panel designed for a circular economy. A combination of ecoinvent and material data sheets were used to analyse a wide range of novel bio-based insulation materials. The screening LCA analysed global warming potential and identified a short-list of promising materials that were then subjected to a detailed LCA for further consideration in the design. The method uses publicly available information and can be applied at material or building-element level. The method thus helps designers estimate environmental impacts without hindering the design process.